"I will defend your right to free speech, provided I agree with you": How social media users react (or not) to online out‐group aggression. Issue 10 (22nd January 2021) - Antonetti, Paolo; Crisafulli, Benedetta
Abstract: Social networking sites (SNS) routinely ban aggressive users. Such bans are sometimes perceived as a limitation to the right to free speech. While research has examined SNS users' perceptions of online aggression, little is known about how observers make trade‐offs between free speech and the desire to punish aggression. By focusing on reactions to an SNS ban, this study explores under what circumstances users consider the protection of the right to free speech as more important than the suppression of aggression. We propose a model of moderated mediation that explains under what circumstances online aggression increases the acceptance of a ban. When posts display aggression, the ban is less likely to be perceived as violating free speech and as unfair. Consequently, aggression reduces the likelihood that users will protest through negative word of mouth. Moreover, users protest against an SNS ban only when this affects an in‐group user (rather than an out‐group user). This in‐group bias, however, diminishes when an in‐group aggressor targets a high warmth out‐group user. The study raises managerial implications for the effective management of aggressive interactions on SNS and for the persuasive communication of a decision to ban a user engaging in aggressive behavior.